GPCR transactivation signalling in vascular smooth muscle cells: role of NADPH oxidases and reactive oxygen species. (14th August 2019) - Mohamed, Raafat; Janke, Reearna; Guo, Wanru; Cao, Yingnan; Zhou, Ying; Zheng, Wenhua; Babaahmadi-Rezaei, Hossein; Xu, Suowen; Kamato, Danielle; Little, Peter J
Abstract : The discovery and extension of G-protein-coupled receptor (GPCR) transactivation-dependent signalling has enormously broadened the GPCR signalling paradigm. GPCRs can transactivate protein tyrosine kinase receptors (PTKRs) and serine/threonine kinase receptors (S/TKRs), notably the epidermal growth factor receptor (EGFR) and transforming growth factor-β type 1 receptor (TGFBR1), respectively. Initial comprehensive mechanistic studies suggest that these two transactivation pathways are distinct. Currently, there is a focus on GPCR inhibitors as drug targets, and they have proven to be efficacious in vascular diseases. With the broadening of GPCR transactivation signalling, it is therefore important from a therapeutic perspective to find a common transactivation pathway of EGFR and TGFBR1 that can be targeted to inhibit complex pathologies activated by the combined action of these receptors. Reactive oxygen species (ROS) are highly reactive molecules and they act as second messengers, thus modulating cellular signal transduction pathways. ROS are involved in different mechanisms of GPCR transactivation of EGFR. However, the role of ROS in GPCR transactivation of TGFBR1 has not yet been studied. In this review, we will discuss the involvement of ROS in GPCR transactivation-dependent signalling.